Dare to Delay? The Impacts of Adolescent Alcohol and Marijuana Use Onset on Cognition, Brain Structure, and Function - Lisdahl, Krista M. (Frontiers in Psychiatry, 2013)
Throughout the world, drug and alcohol use has a clear adolescent onset (Degenhardt et al., 2008). Alcohol continues to be the most popular drug among teens and emerging adults, with almost a third of 12th graders and 40% of college students reporting recent binge drinking (Johnston et al., 2010; Johnston et al., 2009), and marijuana (MJ) is the second most popular drug in teens (Johnston et al., 2010). The initiation of drug use is consistent with an overall increase in risk-taking behaviors during adolescence that coincides with significant neurodevelopmental changes in both gray and white matter (Barnea-Goraly et al., 2005; Giedd, Snell et al., 1996; Gogtay et al., 2004; Lenroot & Giedd, 2006; Paus et al., 1999; Sowell et al., 2004; Sowell, Thompson, Holmes, Jernigan, & Toga, 1999; Sowell, Trauner, Gamst, & Jernigan, 2002). Animal studies have suggested that compared to adults, adolescents may be particularly vulnerable to the neurotoxic effects of drugs, especially alcohol and MJ (see Barron et al., 2005; Cha, White, Kuhn, Wilson, & Swartzwelder, 2006; Monti et al., 2005; Rubino et al., 2009; Schneider & Koch, 2003; Spear, 2010). In this review, we will provide a detailed overview of studies that examined the impact of early adolescent onset of alcohol and MJ use on neurocognition (e.g., Ehrenreich et al., 1999; Fried et al., 2005; Gruber et al., 2011; Gruber et al., 2012; Hanson et al., 2011; Hartley et al., 2004; Lisdahl et al., 2012; McQueeny et al., 2009; Medina et al., 2007; Tapert et al., 2002; Townshend & Duka, 2005; Wilson et al., 2000), with a special emphasis on recent prospective longitudinal studies (e.g., Hicks et al., 2012; Meier et al., 2012; White et al., 2011). Finally, we will explore potential clinical and public health implications of these findings.